МЕТОДЫ ОЦЕНИВАНИЯ ФИНАНСОВОЙ ЭФФЕКТИВНОСТИ ЧАСТНЫХ БИЗНЕС-ПРОЦЕССОВ (Journal of Economic Research & Business Administration, 2015)
In the article are investigated the methods of evaluating the effectiveness in the particular business- processes, which form the briefcase of business- processes ([BP]). Such methods will make it possible to compare the separate directions of business with respect to the effectiveness, to find “bottlenecks” in the briefcase, to evaluate the effectiveness of the replacements of trends in development of business, etc.